Chemical analysis of constitutive pigmentation of human epidermis reveals constant eumelanin to pheomelanin ratio. (22nd September 2015) - Del Bino, Sandra; Ito, Shosuke; Sok, Juliette; Nakanishi, Yukiko; Bastien, Philippe; Wakamatsu, Kazumasa; Bernerd, Françoise
Summary The skin constitutive pigmentation is given by the amount of melanin pigment, its relative composition (eu/pheomelanin) and distribution within the epidermis, and is largely responsible for the sensitivity to UV exposure. Nevertheless, a precise knowledge of melanins in human skin is lacking. We characterized the melanin content of human breast skin samples with variable pigmentations rigorously classified through the Individual Typology Angle (ITA) by image analysis, spectrophotometry after solubilization with Soluene‐350 and high‐performance liquid chromatography (HPLC) after chemical degradation. ITA and total melanin content were found correlated, ITA and PTCA (degradation product of DHICA melanin), and TTCA (degradation product of benzothiazole‐type pheomelanin) as well but not 4‐AHP (degradation product of benzothiazine‐type pheomelanin). Results revealed that human epidermis comprises approximately 74% of eumelanin and 26% pheomelanin, regardless of the degree of pigmentation. They also confirm the low content of photoprotective eumelanin among lighter skins thereby explaining the higher sensitivity toward UV exposure.